2016
DOI: 10.1111/aec.12375
|View full text |Cite
|
Sign up to set email alerts
|

Habitat heterogeneity drives bird species richness, nestedness and habitat selection by individual species in fluvial wetlands of the Paraná River, Argentina

Abstract: We assessed the relationship between habitat heterogeneity and bird species richness and composition within wetlands of the floodplain of the Middle Paraná River, Argentina. Given the high habitat heterogeneity in these wetland systems, we sought to determine whether (i) there was a positive relationship between bird species richness and habitat heterogeneity; (ii) whether bird species richness was associated with certain types of individual habitat types; (iii) whether there was a pattern of species nestednes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
1
28
0
5
Order By: Relevance
“…Different aspects of life histories and ecological attributes among species may provide information with which to predict responses of waterbirds to hydrological fluctuations (Okes, Hockey, & Cumming, ). Because waterbird species use different habitats within floodplains (Colwell & Taft, ; Lorenzón, Beltzer, Olguin, & Ronchi‐Virgolini, ) and because these habitats are affected in different ways by water‐level fluctuations, habitat requirements could be especially important for predicting the responses of waterbird species to hydrological fluctuations in these systems. Changes in the availability of resources as a result of hydrological fluctuations may be related to actual changes in food abundance because prey of waterbirds are also affected by fluvial dynamics (Royan, Hannah, Reynolds, Noble, & Sadler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different aspects of life histories and ecological attributes among species may provide information with which to predict responses of waterbirds to hydrological fluctuations (Okes, Hockey, & Cumming, ). Because waterbird species use different habitats within floodplains (Colwell & Taft, ; Lorenzón, Beltzer, Olguin, & Ronchi‐Virgolini, ) and because these habitats are affected in different ways by water‐level fluctuations, habitat requirements could be especially important for predicting the responses of waterbird species to hydrological fluctuations in these systems. Changes in the availability of resources as a result of hydrological fluctuations may be related to actual changes in food abundance because prey of waterbirds are also affected by fluvial dynamics (Royan, Hannah, Reynolds, Noble, & Sadler, ).…”
Section: Introductionmentioning
confidence: 99%
“…We did not find a correlation between species richness, water level and number of habitats. Thus, although habitat heterogeneity accounts for the spatial variation of species richness at the local scale (Lorenzón et al, 2016), this variable did not explain temporal variation in the regional richness of the fluvial system.…”
Section: Temporal Patterns In Regional Bird Species Richnessmentioning
confidence: 85%
“…We sampled birds over a wide area with substantial environmental heterogeneity in each survey by sampling 60 point counts over approximately 450 km along the fluvial system. The high environmental heterogeneity included in each survey allowed us to sample a high number of spatial niches of the fluvial wetlands, which have been shown to be good predictors of the bird composition of the system (Lorenzón, Beltzer, Olguin, & Ronchi-Virgolini, 2016). The relatively large sample size reduced effects of sampling error on estimates of temporal beta diversity (i.e.…”
Section: Temporal Patterns In Regional Bird Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, wetlands that occur within complexes of different habitat types could contribute to the species that occupy the wetland sites. Breeding season studies assessing the impact of habitat heterogeneity found that different habitat types near wetland sites increased species richness (Lorenzon et al 2016), and this concept can also be applied to winter habitat use due to differing species-specific habitat associations.…”
Section: Introductionmentioning
confidence: 99%